Video - Ibrahim, Adamu Abubakar; Bhatti, Zeeshan; Zeki, Akram M. (IIUM Press, 2015)
Light reflection from an object passes via a video camera lens that is converted into an electronic signal by a special sensor referred to as a charge-coupled device (CCD) (Vaughan, 2010). Top-quality transmitted cameras and even camcorders could have up to three CCDs (each just one for red, green and azure colour) to boost the resolution with the camera and the caliber of the image.